2016
DOI: 10.1128/jvi.02529-15
|View full text |Cite
|
Sign up to set email alerts
|

Simian Immunodeficiency Virus SIVagm Efficiently Utilizes Non-CCR5 Entry Pathways in African Green Monkey Lymphocytes: Potential Role for GPR15 and CXCR6 as Viral Coreceptors

Abstract: African green monkeys (AGM) are natural hosts of simian immunodeficiency virus (SIV), and infection in these animals is generally nonpathogenic, whereas infection of nonnatural hosts, such as rhesus macaques (RM), is commonly pathogenic. CCR5 has been described as the primary entry coreceptor for SIV in vivo, while human-derived CXCR6 and GPR15 also appear to be used in vitro. However, sooty mangabeys that are genetically deficient in CCR5 due to an out-of-frame deletion are infectible with SIVsmm, indicating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
25
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 70 publications
3
25
0
Order By: Relevance
“…Recent work from our laboratory and others has described the use of species-matched non-CCR5 coreceptors by the natural host viruses SIVsmm and SIVagmVer (27)(28)(29). Here we asked whether an SIV of another natural host, SIVagmSab of sabaeus AGM, also utilized species-matched alternative coreceptors in the context of species-matched CD4.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent work from our laboratory and others has described the use of species-matched non-CCR5 coreceptors by the natural host viruses SIVsmm and SIVagmVer (27)(28)(29). Here we asked whether an SIV of another natural host, SIVagmSab of sabaeus AGM, also utilized species-matched alternative coreceptors in the context of species-matched CD4.…”
Section: Resultsmentioning
confidence: 99%
“…We then showed that SM CXCR6 was an efficient coreceptor for SIVsmm in vitro and, using blocking agents, that both CXCR6 and CCR5 were used by SIVsmm for infection of SM peripheral blood mononuclear cells (PBMC) ex vivo (27,28). Subsequently, a study of vervet AGM (which inhabit East and Southern Africa) showed that CCR5 was dispensable for SIVagmVer infection of vervet PBMC, and vervet CXCR6 and GPR15 were robust coreceptors in vitro (29). While that study did not identify the non-CCR5 coreceptor(s) responsible for infection of vervet PBMC, it suggested that the use of alternative pathways to target and enter cells was shared by other natural hosts of SIV.…”
mentioning
confidence: 99%
“…However, additional characterization of CD4 ϩ cell populations in AGM milk as well as of the true extent of chemokine receptor promiscuity for SIVsab milk and plasma variants could elucidate selection pressures leading to compartmentalization. Furthermore, our identification of chemokine receptor promiscuity of chronic SIVsab variants, including a T/F variant, supports the possibility of distinct target cell populations mediating transmission in infant and adult natural SIV hosts (46,(63)(64)(65). Additionally, it is possible, and has been suggested (66)(67)(68), that cell-associated virus is the source of transmitted virus in postnatal transmission.…”
Section: Discussionmentioning
confidence: 74%
“…We next assessed SIVsab variant infectivity in cell lines with distinct chemokine receptor expression of CCR5 and CXCR4, as well as GPR15, as this chemokine receptor has been reported to be utilized as a coreceptor by some SIV strains (20,(43)(44)(45)(46). Chemokine receptor expression was confirmed in the cell lines with virus controls of the CCR5-tropic Du.156.12, the CXCR4-tropic Mn.3, the CCR5-and CXCR4-tropic 89.6, the CCR5-tropic YU2, and the CCR5-and GPR15-tropic YU2-6248wt.…”
Section: Plasma and Milk Sivsabmentioning
confidence: 99%
“…Other mechanisms unique to AGMs that may contribute to disease nonprogression have also been described, including a robust but transient type I interferon response and non-CCR5 entry pathways of SIVagm (29,30). Our findings that homeostatic signals can drive CD4 downregulation give key insights on how AGMs can preserve these essential immune functions while still maintaining a diverse T cell repertoire, as one would expect a skewed representation with some T cell clones more represented than others if the CD4 Ϫ…”
Section: Cd8␣␣mentioning
confidence: 85%